1996
DOI: 10.1111/j.1530-0277.1996.tb01696.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine Treatment Seems to Reduce the Beneficial Effects of Cognitive‐Behavioral Therapy in Type B Alcoholics

Abstract: Alcoholic subtypes identified by cluster analysis seem to be differentially responsive to the effects of fluoxetine treatment on drinking-related outcomes. Serotonergic abnormalities previously identified among a subgroup of alcoholics who are also characterized by impulsivity and severity of alcohol dependence may help to explain the differential medication effect. Based on these findings, it is recommended that, in the absence of a comorbid mood or anxiety disorder, fluoxetine not be used to maintain abstine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
111
2
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(124 citation statements)
references
References 45 publications
8
111
2
3
Order By: Relevance
“…Remarkably, the literature has demonstrated quite the opposite. For instance, Kranzler et al [182] observed that fluoxetine treatment appeared to worsen the clinical benefit of the adjunctive cognitive behavioral treatment and there was no difference from placebo. Actually, Type A-like or late-onset alcoholics, with presumably more normative 5-HT function, have been observed to experience improved drinking outcomes from sertraline both during active treatment [183] and at 6-month follow-up [184].…”
Section: Serotonin Reuptake Inhibitorsmentioning
confidence: 99%
“…Remarkably, the literature has demonstrated quite the opposite. For instance, Kranzler et al [182] observed that fluoxetine treatment appeared to worsen the clinical benefit of the adjunctive cognitive behavioral treatment and there was no difference from placebo. Actually, Type A-like or late-onset alcoholics, with presumably more normative 5-HT function, have been observed to experience improved drinking outcomes from sertraline both during active treatment [183] and at 6-month follow-up [184].…”
Section: Serotonin Reuptake Inhibitorsmentioning
confidence: 99%
“…In fact, only one study of alcoholdependent individuals showed beneficial effects of an SSRI, and that effect was restricted to non-depressed alcoholics (Pettinati et al, 2001) or a subgroup classified as Type A alcoholics (Pettinati et al, 2000). In Type B alcoholics (Dundon et al, 2004;Kranzler et al, 1996) or Type II alcoholics (Chick et al, 2004), SSRIs may increase drinking relative to placebo treatment. In humans, low 5-HT turnover has been associated with increased alcohol-seeking behavior, alcoholism (Virkkunen and Linnoila, 1997), and impulsive violence (Virkkunen et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It was, however, too simplistic to think that Type 2 patients' drinking would therefore become less risky if the patient was prescribed an SSRI. In fact, it seems that Type 2 patients may have a less favourable outcome with SSRIs than placebo (Kranzler et al 1996;Chick et al 2002), or show no response while Type 1 patients benefit (Pettinati et al 2000). And, of course, while higher CSF 5HIAA in these Gerard's studies correlated with increased reproductive fitness, SSRIs in humans are notable for their inhibition of sexual performance.…”
Section: Simplistic Extrapolationsmentioning
confidence: 93%